2010
DOI: 10.1155/2010/630267
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Evaluation in Growing Rats of Diet ContainingBacillus thuringiensisCry1Ia12 Entomotoxin: Nutritional Responses and Some Safety Aspects

Abstract: The Cry1Ia12 entomotoxin from a Brazilian Bacillus thuringiensis strain is currently being expressed in cotton cultivars to confer resistance to insect-pests. The present study aimed to assess the effects of a diet containing Cry1Ia12 protein on growing rats. A test diet containing egg white and Cry1Ia12 (0.1% of total protein) as a protein source was offered to rats for ten days. In addition, an acute toxicity bioassay was performed in rats with a single oral dose of the entomotoxin (12 mg/animal). No adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…No apparent adverse effect was also reported (Sakamoto et al, 2008) in rats fed on GM soy at a level of 30% in the diet for 104 weeks. Some of the studies that reported no adverse effects in animals receiving the test diet containing the Bt Cry1Ia12 protein (Guimaraes et al, 2010) were done not only at a low concentration (0.1%) in the diet but also by feeding rats for a very short duration (10 days).…”
Section: Discussionmentioning
confidence: 99%
“…No apparent adverse effect was also reported (Sakamoto et al, 2008) in rats fed on GM soy at a level of 30% in the diet for 104 weeks. Some of the studies that reported no adverse effects in animals receiving the test diet containing the Bt Cry1Ia12 protein (Guimaraes et al, 2010) were done not only at a low concentration (0.1%) in the diet but also by feeding rats for a very short duration (10 days).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Grossi-de-Sa et al (2007) demonstrated that the recombinant Cry1Ia12 protein, identified in a B. thuringiensis S811 strain and expressed in Escherichia coli cells, was toxic to both cotton boll weevil larvae and fall armyworm ( S. frugiperda ). In addition, Guimarães et al (2010) performed food security assays showing that Cry1Ia12 does not have any toxic effects on mice and thus could be suitable for the production of commercial GM plant varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Although no adverse effects of Cry toxins have been described for humans, safety assessment guidelines have been established to ensure that any product developed from GM crops are safe for human consumption [ 78 , 79 , 80 , 81 ]. Furthermore, the development of a GM plant is not only time consuming but requires previous assurances regarding the toxicity and allergenicity of the introduced foreign proteins to ensure its safety for future commercialization.…”
Section: In Silico Analyses Of Cry and Mutant Tmentioning
confidence: 99%
“…Furthermore, the development of a GM plant is not only time consuming but requires previous assurances regarding the toxicity and allergenicity of the introduced foreign proteins to ensure its safety for future commercialization. Therefore, in vivo assays using Cry1Ia12 have been performed in rats to assess its toxicity against mammals [ 81 ]. Studies using Wistar rats fed Cry1Ia12 toxin did not indicate any significant difference in total weight gain, protein digestibility or nitrogen balance in comparison to rats fed a diet without the Bt toxin.…”
Section: In Silico Analyses Of Cry and Mutant Tmentioning
confidence: 99%
See 1 more Smart Citation